Middle East Geopolitics and the Rise of Multipolarity - Jafaar, Bahrooz. author. aut Link
XI, 194 p. 5 illus., 4 illus. in color.
Keywords: This book explores the shifts in global power from a single dominant superpower to a world with many influential players. Focusing on China’s growing influence through its Belt and Road Initiative, it analyzes the increasing significance of the Middle East as a vital link between the Global North and South. The book further highlights the impact of 'middle powers', which are countries that are not superpowers, but still have a significant influence on global decisions. As technology and non-state actors reshape international politics, these nations are helping to determine the future. Amid growing divisions between global alliances such as NATO and BRICS and a decline in U.S.-China trade, the world is entering a new era. Offering valuable insights into these changes, this book will appeal to students, researchers and policymakers seeking to understand today's complex global landscape.